1989
DOI: 10.1093/oxfordjournals.jhered.a110834
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Inversions and Frequency of Extra Bristles in Natural Populations of Drosophila melanogaster

Abstract: We used isofemale lines derived from 10 populations captured in Asturias, Spain, to estimate variation within and among populations for inversions ln(2L)t, ln(2R)NS, ln(3L)P, ln(3R)P, and ln(3R)C and for the presence of extra dorsocentral and scutellar bristles in first-generation flies. For all populations, the proportion of local isofemale lines with extra bristles was highly correlated with the proportion of flies with inversions. ln(3R)C appears to be mainly responsible for the within-line association of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Unfortunately, despite the experimental tractability of the D. melanogaster model, almost nothing is known about the phenotypic effects of other inversions in this species (Lemeunier & Aulard, 1992). One exception is the finding that the frequency of In(3R)C is correlated with bristle number and that artificial selection for increased bristle number increases the frequency of this inversion (García-Vázquez & Sánchez-Refusta, 1988;García-Vázquez, Sanchez-Refusta, & Rubio, 1989;Izquierdo, García-Vázquez, & Villar, 1991). Moreover, a series of studies showed that In(2L)t heterokaryotypes exhibit overdominance with regard to fecundity and fertility in Japanese populations (Watanabe, 1969;Watanabe & Watanabe, 1973;Watanabe, Watanabe, & Oshima, 1976).…”
mentioning
confidence: 99%
“…Unfortunately, despite the experimental tractability of the D. melanogaster model, almost nothing is known about the phenotypic effects of other inversions in this species (Lemeunier & Aulard, 1992). One exception is the finding that the frequency of In(3R)C is correlated with bristle number and that artificial selection for increased bristle number increases the frequency of this inversion (García-Vázquez & Sánchez-Refusta, 1988;García-Vázquez, Sanchez-Refusta, & Rubio, 1989;Izquierdo, García-Vázquez, & Villar, 1991). Moreover, a series of studies showed that In(2L)t heterokaryotypes exhibit overdominance with regard to fecundity and fertility in Japanese populations (Watanabe, 1969;Watanabe & Watanabe, 1973;Watanabe, Watanabe, & Oshima, 1976).…”
mentioning
confidence: 99%